REPRESENTASI NILAI PERJUANGAN TOKOH UTAMA DALAM NOVEL SARASWATI SI GADIS DALAM SUNYI KARYA ALI AKBAR NAVIS - Tameon, Desi Natalia; Jama , Karolus B.; Djokaho, Margareta P.E. (Yayasan Panca Bakti Wiyata Pangandaran, 2025)
The focus of this research is the value of the struggle of the main character in the novel Saraswati Si Gadis dalam Sunyi Karya Ali Akbar Navis. This research aims to describe the value of the struggle of the main character contained in the novel Saraswati Si Gadis dalam Sunyi. This research is a descriptive qualitative research. The study used in this research is the Sociology of Literature initiated by Hipolyte Taine. The data in this research are in the form of words and sentences. Data collection techniques are done by reading techniques, note-taking techniques and codding techniques. The result of this research shows that Saraswati's character is a strong picture of a disabled person who has determination, empathy, and high spirit in living a challenging life. In the analysis based on Taine's Hipolyte theory, the six values of struggle (the value of patience, the value of self-sacrifice, the value of unyielding spirit, the value of unity, the value of respect and the value of cooperation) do not stand alone, but are formed by three main elements namely Race, Moment, and Environment. First, Race (The value) of patience mostly comes from Saraswati's basic character who is calm, resolute, and not easily discouraged. Saraswati's patience in facing ridicule without verbal resistance shows the inner strength that is born in her. Second, Moment (The value of unyielding spirit and the value of willingness) to sacrifice are also a form of Saraswati's response to the challenges of the times that have not been friendly to people with disabilities. The discriminatory situation and isolation she experienced did not make her retreat, but rather motivated her to fight harder. Third, Environment (The values of unity, respect, and cooperation) are the result of Saraswati's interaction with her environment. Although she is often ostracized, Saraswati still tries to establish relationships and adapt.